2019
DOI: 10.1016/j.ejrad.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a radiomics nomogram for identifying invasiveness of pulmonary adenocarcinomas appearing as subcentimeter ground-glass opacity nodules

Abstract: The aim of the present study was to develop and validate a radiomics-based nomogram for differentiation of preinvasive lesions from invasive lesions that appearing as ground-glass opacity nodules (GGNs) ≤10 mm (subcentimeter) in diameter at CT. A total of 542 consecutive patients with 626 pathologically confirmed pulmonary subcentimeter GGNs were retrospectively studied from October 2011 to September 2017. All the GGNs were divided into a training set (n = 334) and a validation set (n = 292). Researchers extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 39 publications
2
56
1
3
Order By: Relevance
“…In the study by Zhao et al . mean CT value was chosen for distinguishing the preinvasiveness from the invasiveness . We also found a similar result in our study that there was a correlation between the tumor volume and invasiveness.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the study by Zhao et al . mean CT value was chosen for distinguishing the preinvasiveness from the invasiveness . We also found a similar result in our study that there was a correlation between the tumor volume and invasiveness.…”
Section: Discussionsupporting
confidence: 93%
“…26 In the study by Zhao et al mean CT value was chosen for distinguishing the preinvasiveness from the invasiveness. 27 We also found a similar result in our study that there was a correlation between the tumor volume and invasiveness. The mean CT value did not reveal the significant difference in the present study, despite the values being similar in comparison with the data in the study by Zhao et al However, maximal tumor attenuation was another significant factor for the invasiveness reported in our study and was compatible with the study by Li et al 28 Moreover, the mean attenuation of the solid component has been evaluated in a previous study and revealed a significant difference between preinvasiveness and invasiveness.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…В її основі -тривалі (2000-2011 рр.) клінічно апробовані міжнародні експертні дослідження (International association for the study of lung cancer/Аmerican thoracic society/Еuropean respiratory society) пульмонологів, морфологів, радіологів, молекулярних біологів, торакальних хірургів [30,31]. Авторський колектив (понад 50 фахівців) ретельно вивчив більш ніж 500 тематичних публікацій, розробив методологічні засади нової класифікації й довів її до остаточної редакції через запровадження у ряді відомих й авторитетних клінік.…”
Section: âñòóïunclassified